Комп’ютерне моделювання принципів роботи пневматичного циліндра - Тарасов, А. А. (ХНУРЕ, 2025)
This article presents a computer simulation of a pneumatic cylinder, showing its main structural parts. The constructed model allows you to visualize the pneumatic cylinder operation process as a component of an electropneumatic system. The results of this work can be used in the educational process in courses that study pneumatic devices and automation tools for mechatronic systems as a visual demonstration of the principles of operation of pneumatic components.
Keywords: пневматичний циліндр; pneumatic cylinder